Business and Cultural Aspects of Psychic Distance and Complementarity of Capabilities in Export Relationships. Issue 3 (September 2014) - Griffith, David A.; Dimitrova, Boryana V.
Psychic distance is a key element in the field of international marketing. Unfortunately, the literature exhibits a lack of consistency with respect to its effects. To help increase understanding of the influence of psychic distance, the authors investigate business and cultural psychic distance as separate constructs. They develop a model in which an export manager's business and cultural psychic distance influences the structuring of the export relationship (i.e., whether it has complementarity of capabilities) and explore whether business and cultural psychic distance enhances or dampens the leveraging of complementary capabilities to increase an export manager's satisfaction with export performance. The results, based on a survey of 151 U.S. export managers, indicate that when export managers perceive greater business psychic distance, they select export partners with fewer complementary capabilities. Although more complementarity of capabilities results in greater satisfaction with export performance, this relationship is moderated by psychic distance. Specifically, greater cultural psychic distance enhances the positive influence of partner complementarity of capabilities on satisfaction with export performance, whereas greater business psychic distance dampens the positive influence of partner complementarity of capabilities on satisfaction with export performance.